Crianças, infâncias e culturas infantis : epistemologias e subjetividades em narrativas fotoetnográficas - Coelho, Fernanda Mendes Cabral Albuquerque (2018)
This research promotes epistemological and empirical interlocutions on the conceptions of children, childhood and children's cultures through photoetnographic narratives. It holds discussions within the classical approaches of Sociology, Visual Anthropology and Photoetnography in dialogue with the current epistemological perspectives of the Sociology of Childhood that breaks a new social paradigm in modern Science for the studies of the child. Methodologically it is characterized as a transdisciplinary research of interpretative approach and photoetnographic method, that combined different strategies of generation, treatment and data analysis. In view of this, the memento analysis and interpretation movement was initially proposed, which was confronted and discussed in the light of the interpretive, transdisciplinary and critical-cultural rigor of Visual Culture, having its implications discussed in three complementary analytical fields: the first one comprises the image, photography and Photoetnography; the second relates to the Social History of Childhood, the Sociology of Childhood and Visual Culture; and the third presents Photoetnography in an autobiographical perspective as a research strategy with children. Each analytical field required specific methodological strategies, ranging from documentary research, photonnographic research and autobiographical photoetnographic research, the latter of which had as subject one 6-year-old children living in João Pessoa. Thus, the production of photoetnographic narratives in each field of analysis allowed the knowledge, deepening and interpretive disclosure of the reality of childhood reflected in the image of the child thus legitimizing itself as a potential methodological strategy to stimulate the interpretation and understanding of identities, subjectivities and alterities of the child produced in the inter-places and between-cultures of childhood. In view of this, it was found that the photoetnographic narratives of children, in each historical time and cultural context reveal and legitimize a creative and subversive protagonism in the relationships of otherness constituted during childhood, thus, children have developed forms of participation and coping with cultural and social circumstances in which he participates, which is the defense of a new sociological image - that of the child protagonist, a child who subverts the limits and impositions of visual cultures and creatively reinvents ways of being and living in the contemporary world.